The Peptide PbrPSK2 From Phytosulfokine Family Induces Reactive Oxygen Species (ROS) Production to Regulate Pear Pollen Tube Growth - Kou, Xiaobing; Liu, Qian; Sun, Yangyang; Wang, Peng; Zhang, Shaoling; Wu, Juyou (Frontiers in Plant Science, 2020)
Phytosulfokines (PSKs) are plant peptide growth factors that participate in multiple biological processes, including cell elongation and immune signaling. However, little is known about PSKs in Rosaceae species. Here, we identified 10 PSK genes in pear (Pyrus bretschneideri), 11 in apple (Malus × domestica), four in peach (Prunus persica), six in strawberry (Fragaria vesca) and five in Chinese plum (Prunus mume). In addition, we undertook comparative analysis of the PSK gene family in pear and the four other species. Evolutionary analysis indicated that whole genome duplication events (WGD) may have contributed to the expansion of the PSK gene family in Rosaceae. Transcriptomes, reverse transcription-PCR and quantitative real-time-PCR analyses were undertaken to demonstrate that PbrPSK2 is highly expressed in pear pollen. In addition, by adding purified E. coli-expressed PbrPSK2 to pollen and using an antisense oligonucleotide approach, we showed that PbrPSK2 can promote pear pollen tube elongation in a dose-dependent manner. Furthermore, PbrPSK2 was found to mediate the production of reactive oxygen species to regulate pear pollen tube growth.